Interbrain synchrony: on wavy ground. Issue 5 (May 2022) - Holroyd, Clay B.
Abstract : In recent years the study of dynamic, between-brain coupling mechanisms has taken social neuroscience by storm. In particular, interbrain synchrony (IBS) is a putative neural mechanism said to promote social interactions by enabling the functional integration of multiple brains. In this article, I argue that this research is beset with three pervasive and interrelated problems. First, the field lacks a widely accepted definition of IBS. Second, IBS wants for theories that can guide the design and interpretation of experiments. Third, a potpourri of tasks and empirical methods permits undue flexibility when testing the hypothesis. These factors synergistically undermine IBS as a theoretical construct. I finish by recommending measures that can address these issues. Highlights: Interbrain synchrony is a putative neural mechanism said to promote social interactions by enabling the functional integration of multiple brains. Research on this topic has skyrocketed in recent years. However, the field lacks a widely accepted definition of interbrain synchrony. Interbrain synchrony wants for theories that can guide the design and interpretation of experiments. A plethora of empirical methods permit evidence consistent with the idea to accumulate without providing means to falsify it. These problems conspire to undermine the construct validity of the phenomenon. However, steps can be taken to address these issues.